Exploration of validity evidence for core residency entrustable professional activities in Chinese pediatric residency - Li, Shan; Qi, Xin; Li, Haichao; Zhou, Wenjing; Jiang, Zhehan; Qi, Jianguang (Frontiers in Medicine, 2024)
This study seeks to explore validity and reliability evidence for Core residency entrustable professional activities (CR-EPAs) were developed by Peking University First Hospital (PKUFH) in 2020. Methods A prospective cohort study was conducted in PKUFH. Trainers(raters) assessed pediatric residents on CR-EPAs over one academic year, biannually. Critical components within a validity evidence framework were examined: response process (rater perceptions), the internal structure (reliability and contributions of different variance sources), and consequences (potential use of a cut-off score). Results 37 residents were enrolled, and 111 and 99 trainers' ratings were collected in Fall 2020 and Spring 2021, respectively. For rater perceptions, all the raters considered CR-EPAs highly operational and convenient. In all ratings, individual EPAs correlate with total EPA moderately, with Spearman correlation coefficients spanning from 0.805 to 0.919. EPA 2 (Select and interpret the auxiliary examinations), EPA 5 (Prepare and complete medical documents), EPA 6 (Provide an oral presentation of a case or a clinical encounter) and EPA 7(Identify and manage the general clinical conditions) were EPAs correlated with other EPAs significantly. The results of the generalizability theory indicated the variability due to residents is the highest (nearly 78.5%), leading to a large size of the reliability estimates. The matching results indicate that the lowest error locates at 5.933. Conclusions The rating showed good validity and reliability. The ratings were reliable based on G-theory. CR-EPAs have a magnificent internal structure and have promising consequences. Our results indicate that CR-EPAs are a robust assessment tool in workplace-based training in a carefully designed setting.